PENGARUH PROFITABILITAS, PERTUMBUHAN ASET, LIKUIDITAS, STRUKTUR AKTIVA, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Fadjar Harimurti, Narko Prabowo, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2018)
The purpose of this study is to determine whether profitability, asset growth, liquidity, asset structure and sales growth have an influence on the capital structure of the food and beverage manufacturing sector listed on the Indonesia Stock Exchange for the period 2012 – 2016. This study uses a type of quantitative data derived from annual reports which are published on the IDX website (www.idx.co.id) and the website of each company. The population in this study were 16 companies contained in the food and beverage sector companies listed on the IDX, the sampling technique used was purposive sampling, namely a number of 13 selected companies. Data analysis technique uses classical assumption test, multiple linear aggression analysis, t test, F test, and determination coefficient. The results showed that: profitability had no significant effect on the capital structure, asset growth had no effect on the capital structure, liquidity had a significant effect on the capital structure, asset structure had no significant effect on the capital structure, sales growth had no significant effect on the capital structure. Keywords: profitability, asset growth, liquidity, asset structure, sales growth, capital structure